Władze lokalne Zielonej Góry w pierwszych latach powojennych = Zielona Góra local authorities in the first post-war years - Zaradny, Ryszard (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Zielona Góra was organising its social and political life in an environment typical for the post-war period of the Regained Territories, but still distinct from the conditions prevailing in the remaining parts of the country (the so-called ?old part?). The specificity was owed to the population made by people coming to the west from all parts of the pre-war Poland. These inhabitants could not have the feeling of security of their status.
Keywords: Zielona Góra; władza lokalna; historia; po 1944 r.